Upper-body isometric horizontal strength in game sport athletes - Lukas Reichert; Till Müller; Björn Wieland; Marie-Therese Fleddermann; Karen Zentgraf (Frontiers Media S.A., 2023)
Imagine blocking the opposing defense linemen in American football to protect your quarterback or creating gaps in the opponents' defense by setting blocks as a pivot player in handball. Such movements require a pushing action away from the body with the arms and stabilizing the whole body in different postural positions. Upper-body strength obviously plays an important role during American football and handball as well as in other game sports with opponent contact such as basketball. Yet, the availability of appropriate tests to measure upper-body strength serving sport-specific requirements seems limited. Therefore, a whole-body setup to measure isometric horizontal strength in game sport athletes was developed. The purpose of the study was to verify validity and reliability of this setup and present empirical data from game sport athletes. In 119 athletes, isometric horizontal strength was measured in three game-like standing positions (upright, slightly leaning forward and clearly leaning forward), each in three weight-shift conditions (80% of body weight on the left leg, 50/50% on both legs, 80% on the right leg). Also, handgrip strength on both sides was measured in all athletes using a dynamometer. Linear regression indicated that handgrip strength is a significant predictor of upper-body horizontal strength in female (β = 0.70, p = 0.043) but not in male athletes (β = 0.31, p = 0.117). As an expertise-related factor, linear regression indicated that the number of years played at the top level is a predictor of the upper-body horizontal relative strength measure (β = 0.05, p = 0.03). Reliability analyses showed high levels of within-test reliability (ICC > 0.90) as well as test-retest reliability between two separate measurements (r > 0.77). The results indicate that the setup used in this study could be a valid tool for measuring performance-relevant upper-body horizontal strength in different game-like positions in professional game sport athletes.